Assessing social behaviour between baleen whales (Mysticeti) and dolphins (Delphinidae) - Jan-Olaf Meynecke; Olivia Crawley (Discover Animals)
Abstract The dynamics and factors influencing interspecies interactions in the wild are not well understood, particularly among social marine animal species such as Mysticetes and Delphinadae. Baleen whales and various dolphin species have been observed interacting in ways that appear to involve foraging, agonistic and affiliative behavior. Interspecific social interaction might be more common than previously known. With increased use of unmanned aerial vehicles (UAV) and social media reports for cetaceans, interspecies interactions can be examined. Here, we describe instances of baleen whale and dolphin interaction involving 19 species in 199 separate and unrelated events documented by videos and photographs. The most common whale-dolphin interaction involved dolphins swimming near the whale’s rostrum, akin to bow riding. Most observed behaviors can be described as mutual or one-sided playful interactions by dolphins. Understanding whale and dolphin interactions provides insight into their complex social structures and potential interspecies mutualism.